Self-report and urine drug screen concordance among women with co-occurring PTSD and substance use disorders participating in a clinical trial: Impact of drug type and participant characteristics. (1st March 2023) - Ruglass, L.M.; Shevorykin, A.; Zhao, Y.; Killeen, T.K.; Bauer, A.G.; Morgan-López, A.A.; Back, S.E.; Fitzpatrick, S.; López-Castro, T.; Norman, S.B.; Saavedra, L.M.; Hien, D.A.
Abstract: Background: Self-report measures are important in substance use assessment, yet they are susceptible to reporting errors. Urine drug screens (UDS) are often considered a more valid alternative. However, collecting in-person UDS may not always be feasible, contributing to the need to understand factors that influence the validity of self-reported substance use. Methods: In this secondary analysis of data from 295 women with co-occurring PTSD and substance use disorders (SUD) who participated in a clinical trial testing behavioral interventions, we examined concordance and discordance between self-reported drug use and associated UDS results. Generalized linear mixed models were used to examine the impact of treatment type and participant characteristics on the associations between self-reported drug use and UDS results. Results: Findings revealed higher disagreement between self-report and UDS for opioids and sedatives (ranging from.77 to.90) and lower disagreement rates for cannabis and cocaine (ranging from.26 to.33). Treatment type was not a significant moderator of the associations between self-report and UDS across all drugs. Among those with a positive opioid UDS, those who reported employment in the past three years were more likely to self-report no opioid use compared to their counterparts without employment in the past three years. Conclusions: Findings add to the literature that supports the validity of self-reported cannabis and cocaine use. The greater discrepancies between self-report and UDS test results of opioids and sedatives suggest adjunctive UDS may be required, although a variety of factors other than inaccurate self-report may be associated with this discrepancy. Highlights: We examined the agreement between self-reported drug use and associated UDS results. There was a higher disagreement between self-report and UDS for opioids and sedatives. There was lower disagreement between self-report and UDS for cannabis and cocaine. Employment status influenced agreement among those with a positive opioid UDS.